Teacher’s Problem in Blended Learning for Secondary Environment - Ayu Oktaviani; Dewi Syafitri; Sastika Seli (EDULIA: English Education, Linguistic and Art Journal, 2021)
The problem of the research was: “What are the teacher’s problem found in blended learning at SMAN 8 Muara Beliti?”. The objective of the research was to find out the teacher’s problem found in blended learning at SMA N 8 Muara Beliti. The sample of the research was an English Teacher at SMAN 8 Muara Beliti. The samples were taken through Purposive sampling. The researcher used descriptive qualitative research and the data were collected by interview, and documentation. A kind of interview used by the researcher was unstructured interview. Interview and documentation used to identify English teacher’s problem in teaching English when daring and luring process. The data found that, it was difficult to differentiate whether the students understand or not, teacher can nor handle the students efficiently, lost of signal, students left behind and etc. Keyword: Blended Learning, Secondary Environment, Teacher’s Problem,